Isolasi Dan Uji Aktivitas Kitinase Isolat Bakteri Dari Kawasan Geotermal Dieng - Nafisah, Hidayatun; Pujiyanto, Sri; Raharjo, Budi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Chitinase (EC.3.2.2.14) is an enzyme which can degradatechitin became N-acetilglucosamin. Chitinase has many benefits made the demand of it increases. High demands spur its availability in large quantities, cheap, fast production, resistant to any physical factor and chemical environment. Rapid and resistant enzyme production to environment factor can be obtained using chitinolitic bacteria of Geothermal Dieng. The utilization of chitin as bacterial growth substrate from waste of shell crab can be done considering high prices of commercial chitin on the market. The purpose of the research is to get the isolate of termoleranchitinolitic of watery mud in Geothermal Dieng and to know the character of the chosen isolate producing highest chinitase activity type of chitin source treatment and pH of media production. The research is done by growing the chitinolitic in the room temperature for 14 days. The experimental design used in this study is a complete randomized design of factorial pattern (two factors). The first factor is the type of chitin source that includes commercial chitin and chitin crab kits. The second factor is the pH of liquid chitin media for the production of enzymes, ie pH 6, 7 and 8.Chitinase activity is tested by measuring the result of sugar reduction. Obtained data is analyzed with Analysis of Variance (ANOVA). Result of isolation and selection is obtained one potential isolate, KSR 121. The isolate produce 1,4 cm of chitinolitic index after 96 hour incubation. Result of statistical test show both citin source type, pH of media production treatment and interaction were not significantly different (PËƒ0,05). KSR 121 isolate experience the highest growth of crab chitin treatment pH 8 (K2P3) with 6 hour incubation, whereas highest kinitase activity happen on crab chitin treatment pH 7 (K2P2) with 24 incubation, in amount of 0,125 (U/mL).Â Key words: N-acetil glucosamin, chtinase activity, chitinase, chitin, chitinolitic bacteria, isolation